PROMOTIONAL STRATEGY ANALYSIS IN IMPROVING THE ROOMS IN ZODIAK HOTEL KEBON KAWUNG - Taufansyah Firdaus; Indah Nur Agustiani; I Made Dwipa Agastya (TRIKONOMIKA, 2018)
This research aims to analyze the appropriate promotional strategies in increasing the occupancy of the Zodiak Kebon Kawung Hotel Bandung. 15 respondents were taken as a sample of research using purposive sampling from employees of executive sales and executive e-commerce at Zodiak Kebon Kawung Hotel. The analysis used is a SWOT analysis consisting of internal factor analysis factor (IFAS) matrix, external factor analysis summary (EFAS) matrix, external-internal matrix (IE), cartesian diagram and SWOT matrix. These are the position of growth strategy with IFAS score = 2.21, EFAS = 2.50, dan SWOT Matrix; 1) SO strategy ie accessibility of adequate means of transportation, modern hotels; 2) ST strategy that is not expensive and supported by security; 3) WO Strategy that is to improve human resources, facilities and infrastructure of water and sewage treatment, improvement of in-room facilities; 4) WT strategy is to avoid the transfer of educated and experienced personnel.